Knowledge transfer in the context of frugal innovation. (2017) - Neumann, Lukas; Böhm, Jonas; Wecht, Christoph H.
In this paper, we explore knowledge transfer in the context of frugal innovation (i.e., a specific form of resource-constraint innovation). Based on original data from 11 case studies, we observe two distinct clusters. Firms in the cluster 'active' are signified by their direct experience in the target market. Companies in the cluster 'non-active' were not physically present in the target market prior to the frugal initiative. Further, three distinct phases emerged along the value creation process: 1) market research; 2) development; 3) go-to-market. It became evident that firms from the cluster non-active are confronted much more with an influx and outflow of knowledge. Transfer in both directions requires significantly more effort. With this research we contribute to the growing body of literature on frugal innovation and the emerging middle class. We conclude this study with a discussion of the implications of our findings for management practice and research.